MOBILISASI DINI TERHADAP PENYEMBUHAN LUKA PASKA SEKSIO SESARIA DI RSU WAHIDIN SUDIRO HUSODO KOTA MOJOKERTO - Yuni Susanti, Ika (JURNAL KEPERAWATAN SEHAT, 2015)
Most mothers with post partum sectio cesaria feel worried if her body is moved in certain positions will affect post surgery wound that still hasnt fully recouered, also due to the pain that is felt after anesthesia effects is disapparing. The purpose of this study was to determine the effectiveness of early mobilization wound healing sectio caesaria in RSU Wahidin Sudiro Husodo.The type of this research is. analytic cross-sectional. Variabel in this research is mobilization as the independent variable and wound healing post sectio caesarea as the dependent variable. The population of this research that is the entire women sectio caesarea on midwifery room of Wahidin Sudiro Husodo Hospital April 2015 as many as 85 mother. The samples were taken with the technique of sampling concecutive as much as 51 respondents.The results showed that’s from 31 respondents did proper mobilization well as many as of 28 respondents (55%) who ware healing fast and 3 respondents (9.7%) are healing slowly. T test test results obtained results of ρ = 0.00, α = 0.05. Then the Mean α. ρ < H0was rejected and the H1was accepted so there are influences of early mobilization with wound healing.Early mobilization can help the mother post sc speed up the healing wound. the more active early mobilization then the quicker the wound healing.There is a relationship between early mobilization and wound healing. In order to improve the quality of health care health professionals are expected to improve their skills mainly in wound care of post sectio caesarea either through seminars or training to provide a better service.key words : mobilization, wound healing, sectio caesarea